ANALISIS PARAMETRIK ALTERNATIF FONDASI PADA DAERAH TANAH LUNAK (STUDI KASUS: KANTOR BUPATI KAB. ROKAN HILIR, RIAU) - Alfi Fadillah; Budi Susilo Soepandji (Racic : Rab Construction Research, 2024)
A foundation is a part of an engineering system that works by transmitting the load it supports and its own weight into the soil or rock beneath it. In this research, the author plans to compare the bored pile foundation that has been applied to the building with other alternative foundations, namely pile foundation 1 with a depth of 38 meters with a diameter of 0.8 meters, and pile 2 with a depth of 38 meters with a diameter of 1 meter in terms of bearing capacity and the magnitude of the decline that occurred. Then the foundation bearing capacity was calculated using the Meyerhof (1976), McClelland (1974), Skempton (1966), and Reese & O'neill (1999). Single pole reduction using the Vesic (1977) and Poulos & Davis (1980) methods and using the Plaxis v.20 program. Furthermore, the results of the calculations compared the bored pile foundation with pile models 1 and 2. It was found that the bored pile foundation and pile foundation 1 did not meet the permit limit for foundation settlement, only pile foundation 2 met the limit, namely a decrease of less than 10% of the foundation diameter.